2016
DOI: 10.1093/bjsw/bcw054
|View full text |Cite
|
Sign up to set email alerts
|

Referrals and Child Protection in England: One in Five Children Referred to Children’s Services and One in Nineteen Investigated before the Age of Five

Abstract: Based on a Freedom of Information request with data from 75% of all English children's services departments covering over ½ million children, this paper shows that 22.5% of children born in the 2009-10 financial year were referred to children's social care before their fifth birthday. Three-quarters of them were at some point assessed; almost two-thirds found to be in need; and a quarter formally investigated. These findings show the full extent of children's involvement in children's social care before the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 30 publications
2
74
0
2
Order By: Relevance
“…For instance in the United Kingdom, 1 in 5 children born in the 2009–10 was referred to children’s social care before their fifth birthday, and 1 in 19 received a forensic assessment for child maltreatment (Bilson & Martin, 2016). Such intense focus on investigative-forensic assessment contrasts with the slim availability of supportive services for families in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…For instance in the United Kingdom, 1 in 5 children born in the 2009–10 was referred to children’s social care before their fifth birthday, and 1 in 19 received a forensic assessment for child maltreatment (Bilson & Martin, 2016). Such intense focus on investigative-forensic assessment contrasts with the slim availability of supportive services for families in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers described in the vignettes were 10 years younger (ranging in age from [16][17][18][19][20][21][22][23] and held lower-paying jobs than in the standard vignettes (e.g., McDonalds cashier instead of accountant). Otherwise identical to Experiment 1.…”
Section: (N = 164)mentioning
confidence: 99%
“…Today, such situations are far more likely to result in a call to Child Protective Services, with subsequent legal intervention" [15]. A recent study in Britain found that fully one in five children in England born during the 2009-2010 fiscal year were the subject of a call to Child Protective Services before reaching the age of five [16].…”
mentioning
confidence: 99%
“…participants were asked an explicit rationale question: " situations are far more likely to result in a call to Child Protective Services, with subsequent legal intervention" [15]. A recent study in Britain found that fully one in five children in England born during the 2009-2010 fiscal year were the subject of a call to Child Protective Services before reaching the age of five [16]. The effective criminalization of parenting choices that objectively pose little risk to children suggests that additional factors may be at work.…”
Section: (N = 155)mentioning
confidence: 99%